Curcumin Prevented Human Autocrine Growth Hormone (GH) Signaling Mediated NF-κB Activation and miR-183-96-182 Cluster Stimulated Epithelial Mesenchymal Transition in T47D Breast Cancer Cells - Çoker Gürkan, Ajda; Bulut, Derya; Genç, Recep; Ünsal, Zeynep Narçin; Palavan-Unsal, Narcin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (My University, 2019)
Autocrine growth hormone (GH) signaling is a promoting factor for breast cancer via triggering abnormal cell growth, proliferation, and metastasis, drug resistance. Curcumin (diferuloylmethane), a polyphenol derived from turmeric (Curcuma longa), has anti-proliferative, anti-carcinogenic, anti-hormonal effect via acting on PI3K/Akt, NF-κB and JAK/STAT signaling. Forced GH expression induced epithelial mesenchymal transition (EMT) through stimulation of miR-182-96-183 cluster expression in breast cancer cells. This study aimed to investigate the role of NF-κB signaling and miR-182-96-183 cluster expression profile on autocrine GH-mediated curcumin resistance, which was prevented by time-dependent curcumin treatment in T47D breast cancer cells. Dose- and time-dependent effect of curcumin on T47D wt and GH+breast cancer cells were evaluated by MTT cell viability and trypan blue assay. Apoptotic effect of curcumin was determined by PI and Annexin V/PI FACS flow analysis. Immunoblotting performed to investigate the effect of curcumin on PI3K/Akt/MAPK, NF-κB signaling. miR182-96-183 cluster expression profile was observed by qRT-PCR. Overexpression of GH triggered resistant profile against curcumin (20 µM) treatment for 24 h, but this resistance was accomplished following 48 h curcumin exposure. Concomitantly, forced GH induced invasion and metastasis through EMT and NF-κB activation were prevented by long-term curcumin exposure in T47D cells. Moreover, 48 h curcumin treatment prevented the autocrine GH-mediated miR-182-96-183 cluster expression stimulation in T47D cells. In consequence, curcumin treatment for 48 h, prevented autocrine GH-triggered invasion-metastasis, EMT activation through inhibiting NF-κB signaling and miR-182-96-183 cluster expression and induced apoptotic cell death by modulating Bcl-2 family members in T47D breast cancer cells.
Keywords: Meme Kanseri; NF-κB; Epiyelyal-mezenkimal Geçiş; miRNA; Breast Cancer; Epithelial Mesenchymal Transition